(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
There is no common understanding of the digital economy phenomenon in the world today, however, there are many definitions of it. Based on the use of the results of the analysis of processes in the digital economy and the processing of large amounts of data, digital data that can significantly increase the efficiency of storage, sales and delivery of various industries, technologies, equipment, goods and services economic activity, which is considered to be the main factor of production. On the one hand, the lack of a definitive definition of the digital economy is an obstacle to discussing many private and narrowly specialized issues.